Nitric oxide synthase inhibition and glutamate binding in quinolinate-lesioned rat hippocampus - Lisý, V; Stastný, F (Physiological research, 2002)
The effect of lesions induced by bilateral intracerebroventricular (i.c.v.) injection of quinolinate (250 nmol of QUIN/ventricle), a selective N-methyl-D-aspartate (NMDA) receptor agonist, on [3H]glutamate ([3H]Glu) binding to the main types of both ionotropic and metabotropic glutamate receptors (iGluR and mGluR) was investigated in synaptic membrane preparations from the hippocampi of 50-day-old rats. The membranes from QUIN injured brains revealed significantly lowered binding in iGluR (by 31%) as well as in mGluR (by 22%) as compared to the controls. Using selected glutamate receptor agonists as displacers of [3H]Glu binding we found that both the NMDA-subtype of iGluR and group I of mGluR are involved in this decrease of binding. Suppression of nitric oxide (NO) production by N(G)-nitro-L-arginine (50 nmol of NARG/ventricle) or the increase of NO generation by 3-morpholinylsydnoneimine (5 nmol of SIN-1/ventricle) failed to alter [3H]Glu or [3H]CPP (3-((D)-2-carboxypiperazin-4-yl)-[1,2-(3)H]-propyl-1-phosphonic acid; NMDA-antagonist) binding declines caused by QUIN-lesions. Thus, our findings indicate that both the NMDA-subtype of iGluR and group I of mGluR are susceptible to the QUIN-induced neurodegeneration in the rat hippocampus. However, the inhibition of NO synthesis did not reveal any protective action in the QUIN-evoked, NMDA-receptor mediated decrease of [3H]Glu binding. Therefore, the additional mechanisms of QUIN action, different from direct NMDA receptor activation/NO production (e.g. lipid peroxidation induced by QUIN-Fe-complexes) cannot be excluded.
Keywords: buněčná membrána; donory oxidu dusnatého; Kainic Acid; Molsidomine; Quisqualic Acid; agonisté excitačních aminokyselin; tritium; nitroarginin; Glutamic Acid; synthasa oxidu dusnatého; krysa rodu Rattus; Hippocampus; kyselina alfa-amino-3-hydroxy-5-methyl-4-isoxazolpropionová; molsidomin; zvířata; hipokampus; Quinolinic Acid; potkani Wistar; N-Methylaspartate; alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; kyselina chischalová; Excitatory Amino Acid Agonists; Rats, Wistar; Male; degenerace nervu; Tritium; kompetitivní vazba; Nitroarginine; Binding, Competitive; N-methylaspartát; Rats; kyselina kainová; Animals; Cell Membrane; Nitric Oxide Donors; mužské pohlaví; kyselina chinolinová; Nerve Degeneration; Nitric Oxide Synthase; kyselina glutamová